Thailand massacre at the mosque - Journeyman Pictures (United Kingdom : Journeyman Pictures, 2004)
Conflict aroused between muslim communities in South Thailand and the police force. 34 men died in the incident. Soldier fired tear gas and rocket propelled grenades into the Krue Se Mosque.
Keywords: Islamic sociology -- Thailand, Southern; Thailand -- Politics and government; Thailand -- Social conditions